ALLEVIATION OF SALINITY AND DROUGHT STRESS IN CORN PRODUCTION USING A NON-IONIC SURFACTANT - M. R. Chaichi; R. Keshavarz-Afshar; M. Saberi; M. Rostamza; N. Falahtabar (Journal of Animal and Plant Sciences, 2016)
Deficit irrigation strategies have been developed to improve water use efficiency in arid and semi-arid regions. Implementation of deficit irrigation in saline soils, however, is complicated. In a field study, we evaluated if the application of a non-ionic surfactant along with irrigation water can improve the performance of deficit irrigation for corn (Zea mays L.) forage production in a saline soil and water condition. Irrigation regimes were included of full irrigation (no stress), moderate deficit, and severe deficit irrigation. Control plots received irrigation water without surfactant while other plots received water plus surfactant. Moderate and severe deficit irrigation resulted in 12.3 and 22.8% lower forage yield. Surfactant application positively influenced corn forage production, especially when deficit irrigation was induced. Wheat (Triticumaestivum L.) grain yield following corn was also higher in plots that received surfactant during the previous growing season. The results of this experiment showed that treating irrigation water with a non-ionic surfactant significantly enhanced forage yield when full or deficit irrigation regimes were implemented in corn production under soil and water salinity. The effect of surfactant remained in the soil for more than one growing season where wheat yield in the treated plots was higher than that in the control plots in the following growing season. This result clearly demonstrates the potential of surfactant application to improve crop production and WUE under salinity stress.
Keywords: Drought stress; Forage; Salinity; Limited irrigation; Surfactant